Combined Fourier hologram as a noise-resist method of synthesis 2D computer-generated hologram with single diffractive order - Braginets, E.V.; Girnyk, V.I.; Kostyukevich, S.A.; Kurashov, V.N.; Bushma, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
In this paper, a comparative analysis of two approaches to synthesis 2D hologram, which restores optical field without conjugated images, is performed. These holograms are used in embossed rainbow protective holograms to improve their forgeryproof characteristics. As a basis, one method of kinoform hologram synthesis is used, which allows to obtain the restored image of acceptable quality, but phase-matching condition is necessary to complete. That limits usage of this method in mass production of embossed holograms. The offered method of combined holograms is based on addition of optical fields restored by separated Fourier holograms. This method let us to avoid hard requirements to technical process on resist – polymer relief translating accuracy. Thus, the proposed method can be recommended for application in mass production of rainbow protective holograms.